О влиянии ядохимикатов на размножение зайца-русака (Lepus europaeus Pallas) - Алеева, Л.В.; Галака, Б.А.; Шевченко, Л.С. (Вестник зоологии, 1972)
When studying the accumulation of pesticides in L. europaeus it was established that
in an organism of animals caught in a hunting farm of the forest-steppe zone there is
a considerably greater content of DDT than in animals caught in the steppe zone.
A number of young hares from one female to the hunting season in hare population of the
forest steppe zone was 1.1 and in a steppe zone — up to 6.0.
In L. europeus under experiment, in gonads of which above 20 mgjkg of DDT was
found (which corresponds to the quantity of this poison in gonads of hares from foreststeppe zone) some grave disturbances in the generative system are found. The data presented testify to the fact that hare quantity to a considerable extent depends on the biotope \ contamination with pesticides.